The six-spotted spider mite, Eotetranychus sexmaculatus (Riley) (Trombidiformes: Tetranychidae) in Australia, New Zealand, Japan and USA: a revised morphological and molecular-based concept, synonyms, and related species - Beard, Jennifer J.; Beaulieu, Frédéric; Knee, Wayne; Gotoh, Tetsuo (Zootaxa, 2024)
Based on morphological and molecular evidence, Eotetranychus asiaticus Ehara is confirmed as a junior synonym of E. sexmaculatus (Riley). Eotetranychus queenslandicus Manson differs to E. sexmaculatus in some morphological characters states, and currently there is insufficient evidence to confirm if it is also a junior synonym. We therefore propose that it remains a valid species until fresh material can be collected from the type host (Codiaeum variegatum (L.) A.Juss.; Euphorbiaceae) in the type location (Freshwater, Queensland, Australia) for molecular analysis and further comparisons. Eotetranychus sexmaculatus is confirmed as present in Australia and New Zealand. Our analyses indicate that specimens identified as E. sexmaculatus from avocado (Persea americana Mill.; Lauraceae) in Western Australia and New Zealand, and specimens of E. asiaticus from the type host (Ficus erecta Thunb.; Moraceae) and type location (Tomigusuku, Okinawa, Japan) are conspecific with specimens of E. sexmaculatus recently collected from the type host (Citrus sp.; Rutaceae) and type location (Florida, USA), with 0–3.6% divergence in a fragment (451 bp) of cytochrome oxidase subunit I (COI), and 0–0.3% in the ribosomal internal transcribed spacer II (ITS2) gene. Herein we redefine E. sexmaculatus, providing a revised diagnosis, notes on leg chaetotaxy, and variation in the shape of the aedeagus—which is a keystone feature critical for determining species boundaries of spider mite species that have males. Our findings also reinforce the potential of the eupathidion on the palptarsus suζ (i.e. the spinneret) for species diagnoses.